Cyp4a12-mediated retinol metabolism in stellate cells is the antihepatic fibrosis mechanism of the Chinese medicine Fuzheng Huayu recipe - Da-bing Ping; Xin Sun; Yuan Peng; Cheng-hai Liu (BMC, 2023)
Abstract Background Hepatic stellate cells (HSCs), which contain multiple retinol-containing lipid droplets, are important profibrotic cells in liver fibrosis. Under Cyp4a12a/b oxidation, HSC activation was accompanied by the downregulation of genes involved in retinol metabolism, inducing RAE-1 production. By eliminating activated HSCs, NK cells expressing the activating receptor NKG2D are recruited to alleviate fibrosis. FZHY was found to significantly reduce the severity of liver fibrosis by inhibiting the activation and proliferation of HSCs. The molecular processes that govern retinol metabolism, on the other hand, are largely unexplored. This study focused on the regulation of Cyp4a12a/b by FZHY to elucidate the antifibrotic molecular mechanisms underlying the effect of FZHY on retinol metabolism. Methods To investigate mechanisms and altered pathways of FZHY against carbon tetrachloride (CCl4)-induced liver fibrosis based on transcriptomics data. Bioinformatics analysis was used to screen its pharmacological targets. The predicted targets were confirmed by a series of in vitro and in vivo experiments, including mass spectrometry, in situ hybridization, immunofluorescence assays and real-time PCR. Then, the results were further characterized by recombinant adenovirus vectors that were constructed and transfected into the cultured primary HSCs. Results Transcriptomics revealed that Cyp4a12a/b is nearly completely lost in liver fibrosis, and these effects might be partially reversed by FZHY therapy recovery. In vitro and in vivo studies indicated that Cyp4a12a/b deletion disrupted retinol metabolism and lowered Rae-1 expression. Activated HSCs successfully escape recognition and elimination by natural killer (NK) cells as a result of reduced Rae-1. Notablely, we discovered that FZHY may restore the Cyp4a12a/b capability, allowing the recovery of the cytotoxic function of NK cells against HSCs, and thereby reducing hepatic fibrosis by suppressing HSC activation. Conclusion Our findings revealed a new role for Cyp4a in retinol metabolism in the development of hepatic fibrosis, and they highlight Cyp4a12/Rae-1 signals as possible therapeutic targets for antifibrotic medicines.